A Novel miRNA Restores the Chemosensitivity of AML Cells Through Targeting FosB - Wang, Huiwen; Zhan, Huien; Jiang, Xinya; Jin, Lilian; Zhao, Tianming; Xie, Shurong; Liu, Wei; Jia, Yan; Liang, Hui; Zeng, Hui (Frontiers in Medicine, 2020)
The heterogeneous nature of acute myeloid leukemia (AML) and its poor prognosis necessitate therapeutic improvement. Current advances in AML research yield important insights regarding both AML genetics and epigenetics. MicroRNAs (miRNAs) play important roles in cell proliferation, differentiation, and survival and may be useful for AML diagnosis and prognosis. In this study, a novel miRNA, hsa-miR-12462 was identified in bone marrow (BM) samples from AML patients at diagnosis by small RNA sequencing. Significant higher level of hsa-miR-12462 was found in patients who achieve complete remission (AML-CR) after induction therapy compared with those who suffer relapse/refractory (AML-RR). FosB was predicted to the target of hsa-miR-12462 through RNA sequencing, bioinformatics analysis and protein-protein interaction (PPI) network analysis, and then verified by luciferase activity assay. T-5224, the inhibitor of FosB, was administered to AML cell line, which could inhibit cell proliferation, promote apoptosis and restore the sensitivity of AML cells to cytarabine (Ara-C). In summary, higher level of hsa-miR-12462 in AML cells is associated with increased sensitivity to Ara-C via targeting FosB.